PTH-333 Public appreciation of lifestyle risk factors for colorectal cancer and awareness of the nhs bowel cancer screening programme. (22nd June 2015) - Kazmi, SA; Lynes, K; Gilbert, D; Thaha, MA
Abstract : Introduction: Prevention of colorectal cancer (CRC) via reduction of lifestyle risk factors, and participation in bowel screening, are two ways in which public engagement could lower mortality from colorectal cancer. Little is known about the current level of awareness of these factors. This study examined public awareness of lifestyle risk factors and bowel screening, with determination of the factors affecting this. Method: A representative population sample (n = 1500) was surveyed using a study specific postal questionnaire to determine demographics, experience of bowel problems, awareness of lifestyle risk factors, knowledge about the incidence of CRC and potential benefits of screening, as well as personal experience of screening. Statistical analysis was carried out using the unpaired t-test and Chi-square test. Results: The majority of respondents were aged over 50 (74%). 76% had either personal experience or a relative/friend with experience of a bowel problem. The majority of respondents had some awareness of lifestyle risk factors with two thirds answering over 50% of questions correctly. Knowledge of dietary advice was better than risks relating to weight and physical activity. Awareness of lifestyle risk factors was significantly worse in those less than 50 years old (p = 0.0002) and with a lower level of education (p = 0.0019). The majority (62%) were unaware how common bowel cancer is and 44% were unaware that CRC is one of the easiest cancers to cure if caught early. Awareness of bowel cancer diagnosis was significantly lower in those less than 50 years old (p= <0.0001). Respondents were evenly divided over whether the NHS should prescribe exercise and lifestyle changes, with those over 50 years old (p = 0.0126), with no formal education (p= <0.0001) and with no experience of bowel problems (p = 0.0168) being more likely to answer no. Of those who had received a screening kit but not completed it, 30% deemed themselves ineligible, with reasons including being outside the age bracket, having an ileostomy or being under surveillance following previous bowel cancer. By far the most frequent reason for non-completion in eligible respondents was that the process was dirty and unpleasant. Conclusion: The majority of people have some experience of bowel problems. Initiatives are required to improve the awareness of younger people with regard to lifestyle risk factors for CRC, especially since this group stand to benefit most from risk reduction. Those with a lower level of education also had poor awareness but felt that the NHS should not prescribe exercise and lifestyle change; targeting this group would need to take this into account. Disclosure of interest: None Declared.